The Impact of Language on Socioeconomic Integration of Immigrants - Aslan Zorlu; Joop Hartog (Institute of Labor Economics (IZA), 2018)
This study examines the causal effects of Dutch language proficiency of immigrants from four main source countries on their labour market and social integration outcomes. Language proficiency appears ranked according to linguistic distance to The Netherlands, a ranking that even holds for the gender gap in proficiency. We assess the effect of language proficiency on two objective indicators of integration (employment and income) and two subjective measures (feeling Dutch and feeling integrated). The analysis shows that endogeneity of language skills masks a substantial part of language effects. Once accounted for endogeneity, effects of Dutch language proficiency on social and economic integration of immigrants are more than double the estimates ignoring endogeneity.
Keywords: J15; 330; language skills; immigrants; integration; treatment effects